Genetic diversity and relationship among Indonesian local sheep breeds on Java Island based on mitochondrial cytochrome b gene sequences - Alek Ibrahim; Endang Baliarti; I Gede Suparta Budisatria; Wayan Tunas Artama; Rini Widayanti; Dyah Maharani; Luis Tavares; Endang Tri Margawati (Journal of Genetic Engineering and Biotechnology, 2023)
Abstract Background The cytochrome b (Cyt b) gene is one of the most studied mitochondrial DNA (mtDNA) genes to determine sheep’s genetic profile. This study aimed to determine the genetic diversity and relationships of several Indonesian local sheep populations on Java Island, Indonesia, based on the mtDNA Cyt b gene sequences. Blood samples were collected from forty-one individual sheep in seven populations of Indonesia local sheep breeds on Java Island (Priangan = 6, Garut = 6, Batur = 7, Wonosobo = 5, Javanese Thin-Tailed/JTT = 7, Javanese Fat-Tailed/JFT = 5, and Sapudi = 5). DNA extraction was performed on blood samples, and the mtDNA Cyt b gene was amplified using specific primers (Alek-CBF: 5'-CAACCCCACCACTTACAA-3' and Alek-CBR: 5'-CCTTGAGTCTTAGGGAGGTT-3'). The polymerase chain reaction (PCR) products were then sequenced, and data were analyzed using the MEGA version 7.0, DNA SP version 6.0, and NTSYS-pc version 2.11 software. Results A total of 1140 bp complete mtDNA Cyt b gene sequences in this study obtained 1134 monomorphic sites (I), six polymorphic sites (V), one segregation site (S), and five parsimony informative sites (P) with a nucleotide diversity (Pi), the average number of nucleotide differences (K), and sequence conservation (SC) were 0.00119, 1.35610, and 0.9947, respectively. There were six haplotypes consisting of two unique haplotypes and four shared haplotypes with a haplotype diversity (Hd) of 0.5415. The genetic distance within and between populations ranged from 0.0000 to 0.0016 and 0.0000 to 0.0020, respectively. Wonosobo, JFT, and Sapudi sheep have the closest relationship, and then these three breeds were close to JTT sheep, followed by Batur, Priangan, and Garut sheep. Two haplogroups have been found based on the Ovine haplogroup clustering. All Wonosobo, JTT, JFT, Sapudi sheep, and most Batur sheep were clustered into haplogroup B. In contrast, Garut sheep were mostly clustered into haplogroup A, while Priangan sheep were clustered into both haplogroups with the same percentage. Conclusion Seven Indonesian local sheep breeds on Java Island have a close relationship clustered into two haplogroups, namely haplogroups A and B. Most Indonesian local sheep breeds on Java Island in this study were clustered into haplogroup B, except for Garut and Priangan sheep.